Navigating the Energy Intensity Landscape: The Role of Financial Development in Middle-Income Countries - Rosalina, Linda; Wisnu Wibowo (Jurnal Bisnis dan Manajemen, 2025)
Purpose: This study empirically examines the dynamic impact of financial development on energy intensity in 71 middle-income countries (MICs) from 1990 to 2021. MICs, significant contributors to global population and output, face escalating energy demand due to rapid industrialization and urbanization, necessitating a deeper understanding of energy efficiency drivers. The research also controls for trade openness, industrial value added, and economic growth. Methods: Employing the two-step System Generalized Method of Moments (System GMM) dynamic panel data methodology, this study effectively addresses potential issues of unobserved heterogeneity and endogeneity, ensuring robust and reliable findings. Results: The findings reveal that financial development significantly reduces energy intensity in both the short and long run. Economic growth also contributes to a decline in energy intensity. Conversely, trade openness and industrial value-added tend to increase energy intensity. Implications: These results underscore the critical importance of strengthening financial systems and market infrastructure. Such development is crucial for providing sufficient and stable financing for clean energy and energy efficiency projects, supported by targeted financial incentive policies. These measures can significantly accelerate MICs’ transition to cleaner, more efficient energy patterns, thereby fostering sustainable development.